A Bibliography of Islamic Criminal Law - Köndgen, Olaf, (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2021)
In A Bibliography of Islamic Criminal Law Olaf Köndgen offers the most extensive bibliography on Islamic criminal law ever compiled. Drawing on a multitude of sources online and offline A Bibliography of Islamic Criminal Law covers, in its thematic section, not only the classical crime categories of ḥudūd , qiṣāṣ and taʿzīr but also a large number of newly emerging and related fields. In a second section dedicated to countries and eras, Köndgen comprehensively covers the historical and modern application of Islamic criminal law in all its forms. Unlocking the richness of this sub-field of Islamic law with the help of two detailed indices, this innovative reference work is highly relevant for all those researching Islamic law in general and the application of Islamic criminal law over time in particular.